Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Close up of Albert Watkins holding photograph of his grandfather Henry Luise Watkins circa 1900 with haul of tobacco in front of building; Albert in same location